The spatial dimensions of agricultural development in Saudi Arabia(Study in development geography) - Alrashidi, Azizah Marzoug (Journal of Humanities & Social Sciences, 2020)
This research aims to identify the historical development of agriculture in the Kingdom and the impact of high oil and population increase and projects that have been implemented. The researcher relied on theoretical research by selecting the subject of the research and then refer to the sources of the collection of scientific material for research and codification. n this research، I reached a number of conclusions and recommendations، the most important of which is the Kingdom’s self-sufficiency of many agricultural crops، the most important of which are cereals and the superiority of Riyadh city from the rest of the crop area. Conducting technical and economic studies on the types and quantities of non-traditional agricultural resources such as marine fish farms and then assessing their use in light of the limited water resources and environmental conditions that are not suitable for traditional agriculture.